China's Incomplete Military Transformation Assessing the Weaknesses of the People's Liberation Army (PLA) - Chase, Michael S. (RAND Corporation, 2015)
Through extensive primary source analysis and independent analysis, this report seeks to answer a number of important questions regarding the state of China's armed forces. The authors found that the PLA is keenly aware of its many weaknesses and is vigorously striving to correct them. Although it is only natural to focus on the PLA's growing capabilities, understanding the PLA's weaknesses-and its self-assessments-is no less important.